Pembatasan Luas Maksimum Penguasaan Tanah - Ilyas Ismail (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: This article is aimed to explore the rules relating to the limit of maximum land wide owning in terms of balancing land owning fairly. In regard with such purpose, the study on rules and experts perspective is conducted. The findings are that although there are rules regulate the limit of the land owning for agriculture, the rules are providing the chance for imbalance owning that has been put under personal title right and for the corporation with exploration rights. The rule on the limit for buildings is limited to title right for home, and it is based on the minister decree. The rules are tend to imbalance the owning of the land and difficult to fulfill fair ownership. Thus, it is required for the rule regulating the maximum limit of the land either for agriculture or building by looking at the availability and need of it for several necessary.  Maximum Wide Limit of Owning Land